SCHEDULED AND STANDARDISED TRAINING IMPROVED EMPLOYEES' KNOWLEDGE ON GOOD MANUFACTURING PRACTICES (GMP) - Singh, G. K. S.; Azman, K. A. Ku; Hadi, M. A. Abdul; Jaafar, Z.; Affandi, M. M. R. Meor Mohd (International Journal of Pharmacy and Pharmaceutical Sciences, 2018)
Objective: The present study aimed to evaluate the effectiveness of good manufacturing practices (GMP) training in enhancing the awareness of employees from a selected traditional medicine industry towards GMP principles. Methods: This study has employed two methodologies which are the ethnographic and descriptive method. The ethnographic method employed observations and photographs to record the factory facility and documentation system prior and after GMP training. A descriptive method employed data collection through five main sections questionnaire prior and after the completion of GMP training. The data were analysed using statistical package for social sciences (SPSS) version 23.0. Results: The findings from this study revealed that major facility and documentation improvisation were made after training was conducted which were installation of centralized air conditioner and systematic standard operation procedure (SOP) documentation. Results from the questionnaire conducted on GMP revealed significant value with p<0.05. Employees showed average increased percentage of knowledge in all five sections questionnaire which were personnel practices (11 %), premise and equipment (12 %), documentation (9 %), production (4%) and product's quality control (11 %). Conclusion: As a conclusion, we reported that GMP training is crucial to strengthen the employees' knowledge on GMP as to improve products manufacturing quality. Regular training (once a y) keeps the employees updated.